Presence of columnar-lined esophagus is negatively associated with the presence of esophageal varices in Japanese alcoholic men - Yokoyama, Akira (World J Gastroenterol, 2017)
AIM: To determine whether the presence of columnar-lined esophagus (CLE) is associated with the presence of esophageal varices (EVs) in male Japanese alcoholics. METHODS: The subjects were 1614 Japanese alcohol-dependent men (≥ 40 years of age) who had undergone upper gastrointestinal endoscopic screening. Digitalized records of high-quality endoscopic images that included the squamocolumnar junction and esophagogastric junction were retrospectively jointly reviewed by four expert endoscopists for the purpose of diagnosing CLE. The authors investigated whether and to what extent there were associations between the presence of CLE and the presence of EVs, especially in the group with liver cirrhosis (LC). RESULTS: CLE ≥ 5 mm in length was found in 355 subjects (≥ 30 mm in 6 of them), LC without EVs in 152 subjects, LC with EVs in 174 subjects, and EVs without LC in 6 subjects. Advanced EVs, i.e., nodular, large or coiled forms, red color sign, or post-treatment, were found in 88 subjects. The incidence of CLE ≥ 5 mm decreased in the following order (P < 0.0001): 23.3% in the group without EVs, 17.4% in the group with small and straight EVs, and 5.7% in the group with advanced EVs. The multivariate ORs (95%CI) for EVs and advanced EVs in the group with LC were lower when CLE ≥ 5mm was present [0.46 (0.23-0.93) and 0.24 (0.08-0.74), respectively, vs 0-4 mm CLE]. CONCLUSION: The presence of CLE in male Japanese alcoholics was negatively associated with the presence of EVs.